Family Business Practices: Empirical Insights from Bhadrapur Municipality, Jhapa, Nepal - Neupane, Pratik; Luitel, Iswor (Adhyayan Journal, 2025)
This paper reviews the family business practices adopted by different types of business and their approaches. The research is conducted to investigate the management practices and control mechanisms of family business in Bhadrapur area. Primary data showed the responses of the businessmen as well as customers and initiation of family members for undertaking business. A field survey on fifty different types of family businesses and one hundred customers explored the degree of effectiveness of management and control system of the firms. The study has found the trend of business practices along with the frequency of customers’ visit and transactions performed by different income group customers with different family businesses of Bhadrapur area. For the purpose of data presentation and analysis, a business survey as well as customer’s survey were performed by using Likert Scale.The analysis provides foundation for young entrepreneurs and motivates for being self-sustained and establish their own business by their professional skills acquired by degree that they receive from university education. This research will be beneficial for the policy maker of local government.